2019
DOI: 10.1038/s41598-019-49425-1
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic antifungal interactions of amphotericin B with 4-(5-methyl-1,3,4-thiadiazole-2-yl) benzene-1,3-diol

Abstract: Amphotericin B (AmB) is a very potent antifungal drug with very rare resistance among clinical isolates. Treatment with the AmB formulations available currently is associated with severe side effects. A promising strategy to minimize the toxicity of AmB is reducing its dose by combination therapy with other antifungals, showing synergistic interactions. Therefore, substances that display synergistic interactions with AmB are still being searched for. Screening tests carried out on several dozen of synthetic 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 60 publications
4
30
0
Order By: Relevance
“…It is therefore likely that the amine, resorcynyl para-phenolic group, and the remaining heteroatoms of the thiadiazole ring may constitute the vehicle for synergistic action with kanamycin against S. aureus. Previously, the synergistic antifungal interactions were documented to occur between 1,3,4-thiadiazoles and antifungal agent amphotericin B [12]. In this context, the results obtained in our current work confirm that the synergism with various antibiotics is yet another aspect of the biological activity of 1,3,4-thiadiazoles worth investigating.…”
Section: Antibacterial Activitysupporting
confidence: 87%
See 2 more Smart Citations
“…It is therefore likely that the amine, resorcynyl para-phenolic group, and the remaining heteroatoms of the thiadiazole ring may constitute the vehicle for synergistic action with kanamycin against S. aureus. Previously, the synergistic antifungal interactions were documented to occur between 1,3,4-thiadiazoles and antifungal agent amphotericin B [12]. In this context, the results obtained in our current work confirm that the synergism with various antibiotics is yet another aspect of the biological activity of 1,3,4-thiadiazoles worth investigating.…”
Section: Antibacterial Activitysupporting
confidence: 87%
“…Numerous reports have highlighted the antimicrobial, anticancer, antioxidative, or anticonvulsant activities as characteristic of 1,3,4-thiadiazoles [6][7][8]. Due to these interesting features the thiadiazole-derived compounds were extensively studied in our group [9][10][11][12][13], with several 1,3,4-thiadiazole derivatives reported to possess significant acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) inhibition activities rendering them as potential anti-neurodegenerative agents [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, the promising antifungal activity of thiadiazole, thiazine, and thiohydrazide derivatives (el-Shaaer et al, 1997;Matysiak et al, 2000;Magdolen et al, 2000;Vicentini et al, 2002;Singh and Kaushik, 2008) has attracted more attention. In particular, Chudzik et al (2019) demonstrated that 4-(5-methyl-1,3,4-thiadiazole-2-yl)benzene-1,3-diol shows strong synergistic interaction with AmB that significantly reduced the antibiotic concentration required for 100% inhibition of the growth of pathogenic fungi in vitro. Moreover, synergistic interactions were noted for strains with reduced sensitivity to AmB and azole-resistant isolates.…”
Section: Introductionmentioning
confidence: 99%
“…One of the first-line therapies used to fight this infection is the polyene macrolide antibiotic amphotericin B (AmB) [2,3,18,19]. Its mechanism of action is based on the binding of the hydrophobic moiety of the molecule to the ergosterol of the fungal cell membrane, which disrupts the cellular membrane and causes the cytoplasmic content to leak out leading to cell death [20,21].…”
Section: Introductionmentioning
confidence: 99%